Evaluación de largo plazo del efecto de la integración de un robot social en rehabilitación física de marcha asistida por Lokomat (2019)
The present work evidences the development of the long-term study of the integration of a social assistance robot in physical rehabilitation of gait assisted by Lokomat, in addition to the statistical results of the physiological and cognitive variables measured throughout 15 sessions, and of a robotics perception questionnaire implemented during the study. As well as, the statistical results obtained from the social assistance technology perception questionnaire (RAS), aimed at therapists, physiatrists and patients, who have not been assisted or supported by a social robot during the rehabilitation processes, which was developed in institutions in Colombia and Spain.